Biodegradation of polyvinyl chloride by Citrobacter koseri isolated from superworms (Zophobas atratus larvae) - Nyamjav, Indra; Jang, Yejin; Lee, Ye Eun; Lee, Sukkyoo (Frontiers in Microbiology, 2023)
Polyvinyl chloride (PVC) is one of the widely used plastic products worldwide, and its accumulation in the natural environment has become a major global issue with regard to the environment and biotic health. There is accordingly strong demand for the development of solutions and methods for environmental remediation. Degrading plastic waste using microorganisms is an effective and eco-friendly method. However, evidence of bacteria that afford efficient biodegradation of unplasticized, pure PVC film has yet to be reported. Therefore, the biodegradation of PVC becomes very important. Here, we present results on the physicochemical and structural studies of PVC by Citrobacter koseri (C. koseri) isolated from the gut of the superworm, Zophobas atratus (Z. atratus) larvae. We also studied the biodegradability of PVC by the gut microbiota compared with C. koseri. We analyzed the microbial degradation of the PVC surface using field emission scanning electron microscopy (FE-SEM) and energy-dispersive X-ray spectroscopy (EDS) and confirmed that the physical and chemical changes were caused by C. koseri and the gut microbiota. The chemical structural changes were further investigated using X-ray photoelectron spectroscopy (XPS) and Fourier-transform-infrared (FTIR) spectroscopy, and it was confirmed that the oxidation of the PVC surface proceeded with the formation of carbonyl groups (C=O), and hydroxyl groups (-OH) by C. koseri. Additionally, the gut microbiota composed of diverse microbial species showed equal oxidation of PVC compared to C. koseri. Further, we evaluated the capabilities of single bacterial isolate and gut microbiota for pure PVC film biodegradation. Our results verified that C. koseri and the culturable microbiota from the gut of superworms present similar potential to utilize pure PVC film as a carbon source. These findings provide a potential solution for the biodegradation of unplasticized PVC.